Deformable registration for quantifying longitudinal tumor changes during neoadjuvant chemotherapy. Issue 6 (15th July 2014) - Ou, Yangming; Weinstein, Susan P.; Conant, Emily F.; Englander, Sarah; Da, Xiao; Gaonkar, Bilwaj; Hsieh, Meng‐Kang; Rosen, Mark; DeMichele, Angela; Davatzikos, Christos; Kontos, Despina
<x xml:space="preserve">Abstract</x> Purpose To evaluate DRAMMS, an attribute‐based deformable registration algorithm, compared to other intensity‐based algorithms, for longitudinal breast MRI registration, and to show its applicability in quantifying tumor changes over the course of neoadjuvant chemotherapy. Methods Breast magnetic resonance images from 14 women undergoing neoadjuvant chemotherapy were analyzed. The accuracy of DRAMMS versus five intensity‐based deformable registration methods was evaluated based on 2, 380 landmarks independently annotated by two experts, for the entire image volume, different image subregions, and patient subgroups. The registration method with the smallest landmark error was used to quantify tumor changes, by calculating the Jacobian determinant maps of the registration deformation. Results DRAMMS had the smallest landmark errors (6.05 ± 4.86 mm), followed by the intensity‐based methods CC‐FFD (8.07 ± 3.86 mm), NMI‐FFD (8.21 ± 3.81 mm), SSD‐FFD (9.46 ± 4.55 mm), Demons (10.76 ± 6.01 mm), and Diffeomorphic Demons (10.82 ± 6.11 mm). Results show that registration accuracy also depends on tumor versus normal tissue regions and different patient subgroups. Conclusions The DRAMMS deformable registration method, driven by attribute‐matching and mutual‐saliency, can register longitudinal breast magnetic resonance images with a higher accuracy than several intensity‐matching methods included in this article. As such, it could be valuable for more accurately quantifying heterogeneous tumor changes as a marker of response to treatment. Magn Reson Med 73:2343–2356, 2015. © 2014 Wiley Periodicals, Inc.